CODING GAMES AS A MEDIUM TO STIMULATE COMPUTATIONAL THINKING IN CHILDREN AGED 5-6 - Amalia Destivani; Agus Khunaifi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to determine how coding games can be used as a medium to stimulate computational thinking in children aged 5–6 years at RA Hj. Sri Musiyarti. The study used data validity tests through observation, interviews, and documentation. The results showed that coding games can stimulate children's abilities in arranging sequences of steps, recognizing patterns, predicting the consequences of instructions, and performing simple debugging. This coding play activity also strengthens social skills such as cooperation, communication, and the ability to manage emotions during the problem-solving process. Coding games are an effective medium in stimulating the basics of computational thinking in early childhood and are suitable for integration into the Early Childhood Education curriculum to support children's readiness to face the demands of 21st-century learning.